Membangun Generasi Gemar Membaca Melalui Dongeng Interaktif - Adinda Ramadani Alenita; Jiya Nurul Anggreani; Siti Nur Hidayah; Zenita Rofikoh (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2025)
Reading is a highly beneficial activity for gaining information, knowledge, and insights. When the children are encouraged to develop reading habits from an early age, they are likely to grow into individuals who enjoy reading. During this crucial and education phase, children exhibit creativity, imagination, and honesty in their thoughts and emotions. However, according to UNESCO, the literacy rate in Indonesia remains relatively low. Through the use of interactive storytelling in childrens’s education, thin community service projecta aims to promote a culture of reading. The first step in the initiative involves providing media that highlight the benefits of interactive storytelling in enhancing children’s reading interest. This method is expected to offer a fun and engaging learning experience while fostering children’s creativity, imagination, and critical thinking skills. Interactive storytelling also serves as an effective teaching strategy to support the holistic development of children.